E-Module Based on Ncesoft Flip Book Maker for Primary School Students - Dwi Yasa, Arnelia; Delawanti Chrisyarani, Denna; Akbar, Sa’dun; Mudiono, Alif (International Journal of Engineering and Technology, 2018)
The purpose of this study is to develop a prototype of e-module based on Ncesoft Flip Book Maker in thematic learning. The research and development method used is the Dick, Carrey and Carrey model. Out of the 10 stages in this model, the researcher stopped at the 7th stage, namely developing and selecting learning material. The subject of this research is a group of fifth grade elementary school students in Indonesia who are involved in 2013 curriculum thematic learning. The result of this developmental research is producing an e-module prototype using the Ncesoft Flip Book Maker application. The development of e-module based on Ncesoft Flip Book Maker can help educators to develop other learning e-modules that are versatile and can support other needs.Â Â